Towards the institutionalization of divorce mediation in Nigeria: a case study of Enugu State - Anidi, Ugochinyelu Chikodili Nerissa (Department of Private Law, 2020)
Nigerian divorce laws and the divorce litigation process pose severe psychological, social-cultural, economic, and legal problems for families going through divorce in Nigeria. This thesis argues that divorce mediation may be able to ameliorate the harsh effects of these laws and process. This thesis seeks to achieve the following objectives: (1) To determine if the divorce mediation process can achieve the goals of a good divorce process, (2) To determine if the divorce mediation process can provide solutions to the myriad of unique problems which face families going through divorce in Nigeria, and (3) To determine the possibility of incorporating divorce mediation into the family dispute resolution system in Nigeria through an institutionalized divorce mediation program at the government-funded citizens' mediation centres. These objectives are achieved through an in-depth review of the customary and statutory laws regulating marriage and divorce in Nigeria as well as a review of the divorce litigation process in Nigeria. This thesis employs both desk and empirical research methods. It examines legislation, policy documents and academic treatises on divorce and divorce mediation. It also utilizes semistructured interviews to examine the Citizens' Rights and Mediation Centre, Enugu State, to determine its viability as a vehicle for the institutionalization of divorce mediation in Nigeria. The thesis finds that indeed divorce mediation achieves the aims of good divorce law. It further finds that while the divorce mediation process is not a panacea, its features lend themselves easily to the resolution of the myriad of problems which face families going through divorce in Nigeria. It also finds that divorce mediation can be incorporated into the Nigerian family dispute resolution system through an institutionalized divorce mediation program at the state-funded citizens' mediation centres present in several states in the country. It concludes that incorporating divorce mediation into the family dispute resolution system in Nigeria will ameliorate some of the harsh effects of the current divorce system. It offers short and long term proposals for the institutionalization of divorce mediation in Nigeria.